Efficacy of Red Blood Cell Exchange as Adjunctive Treatment for Hypoxemia and Survival Rate of Patients With Severe Coronavirus-2 Disease: An Open-Labeled Phase 2 Randomized Clinical Trial - Aminianfar, Mohammad; Soleiman-Meigooni, Saeed; Hamidi-Farahani, Ramin; Darvishi, Mohammad; Hoseini-Shokouh, Seyyed Javad; Asgari, Ali; Faraji-Hormozi, Syrous; Asli, Maryam (Frontiers in Medicine, 2022)
Background Severe acute respiratory syndrome (SARS) coronavirus-2 may infect red blood cells (RBCs) and impact oxygenation. We aimed to evaluate the efficacy of RBC exchange as an adjunctive treatment for hypoxemia and the survival rate of patients with severe coronavirus disease 2019 (COVID-19). Methods In a randomized clinical trial, we divided sixty patients with severe COVID-19 into two groups. The intervention group received the standard treatment of severe COVID-19 with RBC exchange three to four times in 2 days. The control group only received the standard treatment. Our primary outcomes were improving hypoxemia in 7 days, recovery or discharge, and death in 28 days. We conducted Chi-square test, independent samples t-test, and Fisher’s exact test to analyze the results. The ethical committee of Aja University of Medical Sciences approved the study (IR.AJAUMS.REC.1399.054), and the Iranian clinical trial registration organization registered it (IRCT20160316027081N2). Results Twenty-nine men and thirty-one women with a mean age of 67.5 years entered the study. The frequency of hypertension and diabetes mellitus was 86.7 and 68.3%, respectively. The most common symptoms of severe COVID-19 were dyspnea (91.6%), cough (75%), and fever (66.6%). Our results showed that hypoxemia improved in 21 of the 30 patients (70%) in the intervention group and 10 of the 30 patients (33.3%) in the control group (P < 0.004). The recovery and discharge rates were 19 of 30 patients (63.3%) in the intervention group and 2 of 30 patients (6.7%) in the control group (P < 0.001). Conclusion The RBC exchange improved the oxygenation and survival rate in patients with severe COVID-19.